The relationship between seismic and aseismic slip on the Philippine Fault on Leyte Island: Bayesian modeling of fault slip and geothermal subsidence - Dianala, JDB; Jolivet, R; Thomas, MY; Fukushima, Y; Parsons, B; Walker, R (American Geophysical Union, 2020)
Delineating seismic and aseismic slip on faults allows the exploration of the complex relationship between these different modes of slip. Further, quantifying them helps in the assessment of seismogenic potential. We present a distributed slip model of the rate of aseismic slip along the Leyte island section of the Philippine Fault and make comparisons with the extent of seismic slip from the latest significant earthquakes in July 2017. We derived both coseismic and aseismic slip distributions from kinematic inversions of synthetic aperture radar interferometric (InSAR) observations using a probabilistic (Bayesian) framework. Velocity maps from stacking and time series analysis of ALOS interferograms spanning 4 years (2007–2011) show a step change in ground deformation right on the fault. Inverting for slip at depth reveals along-strike variations of aseismic slip rate over ∼100 km. Aseismic slip on the surface reaches rates of more than 3 cm/yr, equivalent to the long-term slip rate (3.3 ± 0.2 cm/yr). Over the same period, a 20-km segment in Tongonan appears to be locked. This segment ruptured in Mw 6.5 and Mw 5.8 earthquakes on 6 and 10 July 2017, respectively, as constrained by Sentinel-1 and ALOS-2 InSAR data. Seismic slip appears to be restricted within the Tongonan segment, with up to 152 ± 21 cm of left-lateral displacement. The slip budget and complementarity between the extents of interseismic and coseismic slip suggest that a seismogenic asperity exists in Tongonan. The presence of active hydrothermal systems and rate-strengthening materials provide physical conditions that can promote aseismic slip.